Oncogenes - the basics - Ghosh, Arnab; Ghartimagar, Diasma; Thapa, Sushma (Journal of Biomedical Sciences, 2018)
Normal cell cycle and cell proliferation are regulated by several genes which can be broadly classified into 4 groups viz, proto-oncogenes, tumor suppressor genes, genes regulating apoptosis and genes involved in DNA repair. These genes may be defective due to different factors. The defective genes may lead to production of abnormal proteins which may lead to disruption of the normal cell cycle and proliferation. A single precursor cell with defective gene proliferates surpassing the normal physiologic regulatory process and leads to tumor formation, so, traditionally,it is said that “tumors are clonal”.